Nutritional approach based in self-compassion versus energy-restricted diet approach in body dissatisfaction and disordered eating in adult women: a protocol for randomized clinical trial - Alessandra Behar Ramos; Vinícius Suedekum da Silva; Débora Viçosa Cardoso; Carolina Guerini de Souza (PLoS ONE, 2025)
The proposed study protocol aims to compare the effect of a nutritional approach based on self-compassion techniques compared to the traditional method through dieting on body image dissatisfaction, caloric restriction, and dysfunctional eating in women who feel dissatisfied with their bodies. Materials and methods This protocol was developed according to the guidelines of the Standard Protocol Items: Recommendations for Interventional Trials 2013 Statement (SPIRIT) and presents a randomized clinical trial with women who are dissatisfied with their bodies and live in southern Brazil. Participants will be randomized to the self-compassion or diet group and attend eight-week weekly meetings. Body image dissatisfaction will be assessed using the Body Shape Questionnaire (BSQ), dysfunctional eating will be assessed using the Three Factor Eating Questionnaire (TFEQ-RS21), and levels of self-compassion will be measured using the Self-Compassion Scale (SCS). The participants will answer the tools at the beginning of the study, at the end of the 8-week intervention, and 3 and 6 months after the end of the meetings. Discussion This will be the first study to compare these two approaches using body dissatisfaction and eating behavior as outcomes, not just body weight. To date, only observational studies have evaluated the relationship between self-compassion, body dissatisfaction, and dysfunctional eating behavior. Trial Registration: ClinicalTrials.gov NCT06084260